DOES WORKING CAPITAL HAS AN IMPACT ON PROFITABILITY OF INDIAN STEEL INDUSTRY - Bhatt, Anil K.; Shrotriya, Nirmala (International Journal For Research In Business, Management And Accounting, 2017)
Working capital has a major role in day to day business activities. It is simply defined as the excess amount of current assets over current liabilities. Working capital also means the fund which is needed for the operations which are taken place in a firm every day. So working capital is considered as a fund which revolves all the time. This revolving fund consists of continues conversion of cash and raw materials in to inventory, then inventory to sales or debtors and this debtors into cash or investment. The existing Working capital in the company is also commonly known as Net Working Capital or net current assets, is the excess if current assets over current liabilities. But this is on a particular day i.e., 31st March’s position. While it is important to know whether the company really has correct level of WC which is required to them? For this purpose there is a need to find out the required working capital and its relation with the profitability. Thus, the research work has included measuring the impact of WC on profitability. Further there must be discussions with the accounting experts of the selected 10 steel companies to know what they feel about their desired level and actual level of working capital.